PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN YANG TERDAFTAR PADA CORPORATE GOVERNANCE PERCEPTION INDEX - Susanti, Depa; M. Rasuli, M. Rasuli; Wijaya, Errin Yani (Jurnal Tepak Manajemen Bisnis, 2016)
The purpose of this research is to disclose influence of applicating Good CorporateGovernance (GCG) to financial performance. A measure of Corporate Governance implementation isCGPI score A measure of corporate performance is Return On Equity (ROE), Return On Investment(ROI) and Earning Per Share (EPS).The statistical method used is simple regression analysis. Sampling was purposive sampling techniqueis the selection of samples with specific criteria, so that samples obtained in this study as ma ny as 9companies. The statistical software used was the software Statistical Product and Service Solutions(SPSS) version 17.00 for Windows with T test, simple linear regression and Classical Assumption Test.The result from this research shows that significant effect on the Implementation of Good CorporateGovernance to Return on Equity and there are no significant effect partial implementation of GoodCorporate Governance to Return On Investment and Earnings Per Share.